Analysis of NGOs Competitive Strategies in Kenya a Case of HIV/AIDS Focused NGOs - Arasa, Robert; Kioko, Mary (My University, 2014)
The NGO sector has experienced rapid growth in therecent years coupled with cut-backs in donor funding due to the global economic downturn. This has led to increased competition among NGOs for dwindling financial resources. NGOs are therefore forced to come up with strategies to compete for these scarce resources in order to survive, to ensure continuity of their programs and to accomplish their organizations missions. The study examined strategies employed by these NGOs in competing for donor funding and their effectiveness.Descriptive research design was adopted for this study and data was collected through the survey-questionnaire method. The target population consisted of NGO’s operating in Nairobi under the HIV/AIDS sector. Data collected was analyzed using descriptive statistics.Findings reveal that most effective strategies utilized by NGOs in the sector for accessing donor funding are the positioning and internal development strategies. Those effective when used in combination are positioning strategy and internal development strategy and, positioning strategy and cooperative strategy. The study suggests that NGO’s should focus on positioning, internal development and cooperative strategies when seeking donor funding within a competitive environment. Further,studies could be conducted to analyze major policy decisions that shape allocation of funds by donors. A comparative study can also be conducted on competitive strategies adopted by not-for-profit organizations and for-profit organizations
Keywords: Competitive strategies; Donor funding; Effectiveness; NGO; Kenya